Recent Advances and Contribution of Synthetic Aperture Radar (SAR) Applications for Agricultural Monitoring - Ajadi, Olaniyi; McAlpin, David (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Following on from the Special Issue "Recent Advances and Contribution of Synthetic Aperture Radar (SAR) Applications for Agricultural Monitoring", we concluded that SAR has now become a pivotal sensor for agricultural monitoring. In this Special Issue, you will find a variety of background material discussing SAR and its applications. Several papers focused on using machine learning approaches with SAR to monitor crop stages and classify crops, while others focused on the polarimetric mode to estimate crop height. Going forward, we hope that you will find this Special Issue to be a useful reference.